2003
DOI: 10.1021/bk-2003-0847.ch020
|View full text |Cite
|
Sign up to set email alerts
|

Phenothiazine Photosensitizers for Onium Salt Photoinitiated Cationic Polymerization

Abstract: The syntheses of several different substituted phenothiazines are described and the ability of these compounds to photosensitize the photolysis of different onium salt cationic photoinitiators is described. These photosensitizers (PS) are generally operative in the mid-and long-range regions of the UV spectrum. The efficiencies of photosensitization of the cationic photopolymerizations of several typical epoxide and vinyl ether monomers by different substituted phenothiazine compounds were evaluated and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…To verify the presence of a potential gradient between the donor, the antenna, and the acceptor suitable to induce charge separation, we compute the ground- and excited-state redox potentials of each subunit following the procedure described in section . As shown in Table , the redox values calculated at the B3LYP/DCM (COSMO) level compare well with the experimental cyclic voltammetry onset values. ,, These results overall confirm the validity of the applied method and computational setup. Considering also the positive results obtained with TD-DFT, the choice of the hybrid B3LYP functional appears to be appropriate for studying the electronic and optical properties of molecular complexes employing these functional subunits.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…To verify the presence of a potential gradient between the donor, the antenna, and the acceptor suitable to induce charge separation, we compute the ground- and excited-state redox potentials of each subunit following the procedure described in section . As shown in Table , the redox values calculated at the B3LYP/DCM (COSMO) level compare well with the experimental cyclic voltammetry onset values. ,, These results overall confirm the validity of the applied method and computational setup. Considering also the positive results obtained with TD-DFT, the choice of the hybrid B3LYP functional appears to be appropriate for studying the electronic and optical properties of molecular complexes employing these functional subunits.…”
Section: Resultssupporting
confidence: 75%
“…As shown in Table 1, the redox values calculated at the B3LYP/DCM (COSMO) level compare well with the experimental cyclic voltammetry onset values. 19,20,23 These results overall confirm the validity of the applied method and computational setup. Considering also the positive results obtained with TD-DFT, the choice of the hybrid B3LYP functional appears to be appropriate for studying the electronic and optical properties of molecular complexes employing these functional subunits.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…These hydroxyl groups enhance solubility of the photosensitizer in the epoxy monomer and also reduce toxicity of the photosensitizer by forming covalent bonds with terminating ether groups in the polymer chain [ 68 ]. Gomurashvili and Crivello [ 69 ] reported dual property of phenothiazines as photosensitizers as well as co-monomers in the cationic ring opening polymerization of various epoxide monomers. These polymerizable photosensitizers also possessed an absorption maximum between 254–333 nm and were able to speed up the cationic ring opening polymerization of various epoxides [ 70 ].…”
Section: Onium Salt Photoinitiators For Different Epoxy Monomersmentioning
confidence: 99%
“…As previously mentioned, the UV light irradiation of cytochrome c with low concentrations of phenothiazines at pH 8.0 led to protection of the protein against photo-damage and increased the turbidity of the samples. Literature data [29,37] and our laboratory results (unpublished) have demonstrated that phenothiazinescation radicals can oligomerize and form nanostructures in the presence and in the absence of polymers such polyethylene glycol. Consistently, in the conditions in which a reduced form of cytochrome c was detected by UV-visible spectroscopy, a significant increase of baseline was also present (Figures 2C, 2F, 3B and 3E, dotted lines).…”
Section: Resultsmentioning
confidence: 82%